Pengaruh Pengungkapan Corporate Social Responsibility terhadap Cost Of Equity Perusahaan - Mitta Ariyani; Yeterina Widi Nugrahanti (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2016)
AbstractThe purpose of this study is to investigate the effect of Corporate Social Responsibility (CSR) Disclosure on Cost of Equity Capital. CSR disclosure index is measured based on Global Reporting Initiative standards, while Cost of Equity Capital is measured by Capital Asset Pricing Model (CAPM). This study uses manufacturing companies which is listed on Indonesia Stock Exchange (IDX) in 2010. By purposive sampling, this research obtained 72 companies as a samples. The control variables used are financial leverage and firm size. Multiple regression analysis by SPSS 16 was run for testing the hypothesis. The result show that CSR disclosure and financial leverage have no effect to Cost of Equity. Then, firm size have positive effect to Cost of Equity.